2013
DOI: 10.1055/s-0033-1333695
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Concurrent Training on Explosive Strength and VO2max in Prepubescent Children

Abstract: The purpose of this study was to compare the effects of an 8-weeks training period of resistance training alone (GR), combined resistance and endurance training (GCON) and a control group (GC) on explosive strength and V(O2max) in a large sample of prepubescent boys and girls. 125 healthy children (58 boys, 67 girls), aged 10-11 years old (10.8±0.4 years) were assigned into 2 training groups to train twice a week for 8 weeks: GR (19 boys, 22 girls), GCON (21 boys, 24 girls) and a control group (GC: 18 boys, 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 23 publications
10
27
0
Order By: Relevance
“…Although studies have shown a meaningful effect of plyometric training on endurance performance (Barnes & Kilding, 2015), a relatively novel finding to this study is the improvement of endurance performance in a test with repeated changes of direction such as the 20 m shuttle run endurance test, which might be more specific for soccer players . This improvement might be related with a better running economy (Marta, Marinho, Barbosa, Izquierdo, & Marques, 2013), which in turn might be explained by decreased ground contact times, increased musculotendinous stiffness, elastic energy return (Barnes & Kilding, 2015;Spurrs, Murphy, & Watsford, 2003), neuromuscular activity or enhanced running mechanics (Barnes & Kilding, 2015). However, direct assessment of potential mechanisms that could improve endurance performance after plyometric training deserves further consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Although studies have shown a meaningful effect of plyometric training on endurance performance (Barnes & Kilding, 2015), a relatively novel finding to this study is the improvement of endurance performance in a test with repeated changes of direction such as the 20 m shuttle run endurance test, which might be more specific for soccer players . This improvement might be related with a better running economy (Marta, Marinho, Barbosa, Izquierdo, & Marques, 2013), which in turn might be explained by decreased ground contact times, increased musculotendinous stiffness, elastic energy return (Barnes & Kilding, 2015;Spurrs, Murphy, & Watsford, 2003), neuromuscular activity or enhanced running mechanics (Barnes & Kilding, 2015). However, direct assessment of potential mechanisms that could improve endurance performance after plyometric training deserves further consideration.…”
Section: Discussionmentioning
confidence: 99%
“…In young soccer players, PT may not induce a significant increase in V _ O 2 max (31) or lactate threshold (11) but may increase the performance during an intermittent test that implicates repeated and sudden changes of direction (46), increase that may be related to improved neuromuscular and anaerobic characteristics. Also, an increased neuromuscular ability (i.e., RSI) may be transferred into improved running economy (26) that, independent of V _ O 2 max, lactate threshold, among others "aerobic" indicators, may affect endurance (35).…”
Section: Discussionmentioning
confidence: 99%
“…The authors speculated that excessive fatigue resulting from the concurrent training regimen may have compromised both strength and endurance adaptations (18). Interestingly, the blunting of strength adaptation which is often observed in adult performers when both strength-and endurance-training are included in the same training session (90) appears not to occur in children (53) and adolescents (75,76). As the interference phenomeon is mediated by training volume and recovery from sessions (5), it seems likely that the volumes of each training modality included in the aforementioned studies were insufficient to negatively impact upon strength-related adaptation.…”
Section: Efficacy In Adolescent Runnersmentioning
confidence: 99%